Acquired immune deficiency syndrome without the recognized risk factors. Issue 744 (October 1987) - Rademaker, M.; Thomas, R. H.; Provost, T. G.; McEvoy, M.; Grint, P. C.; Heath, R.; Kirby, J. D.
Abstract : We report two cases of acquired immune deficiency syndrome (AIDS), apparently without the usual exposure factors, in whom a temporal association was detected after detailed epidemiological investigation. The index case, a 45 year old housewife, had provided terminal home-nursing care for a 33 year old African man, who died from an undiagnosed encephalitis. At that time she had fissures of the skin of both her hands. Review of post-mortem pathology specimens of the African man allowed a retrospective diagnosis of AIDS with cerebral toxoplasmosis to be made. The type of home-nursing care given by the index case was quite different from that normally provided by health care workers with the training and facilities to prevent the spread of infection.